Primary spontaneous cerebrospinal fluid leaks located at the clivus - Van Zele, Thibaut (OceanSide Publications, Inc., 2013)
Transclival meningoceles and primary spontaneous cerebrospinal fluid (CSF) leaks at the clivus are extremely rare lesions and only few of them have been reported in the literature. We report here six cases of transclival primary spontaneous CSF leaks through the clivus. A retrospective case study was performed. We reviewed six cases involving sinonasal CSF leaks located at the clivus treated between 1997 and 2009. Presenting symptoms, duration of symptoms, defect size, site of defect, surgical approach and technique of defect closure, intraoperative complications, postoperative complications, and recurrences are discussed. All CSF leaks were located in the upper central part of the clivus. two of six patients showed signs of increased intracranial pressure (ICP) including arachnoid pits and/or empty sella. For three patients a purely transnasal approach was used with multilayer reconstruction using a nonvascularized graft, and three patients underwent a transnasal transseptal approach with a multilayer reconstruction, with nasoseptal flap. No recurrences of CSF leaks at clivus or other sites were observed to date with a mean follow-up of 10.3 years (range, 3–15 years). Spontaneous CSF rhinorrhea located at the clivus is an extremely rare condition. To date, only eight cases have been described. Here, we report the largest group of six consecutive cases. Irrespective of the used reconstruction technique in all cases a 100% closure rate was achieved. However, identification of increased ICP is an essential aspect and this condition should be treated either medically or surgically.